Oxidative Difunctionalization of Alkenyl MIDA Boronates: A Versatile Platform for Halogenated and Trifluoromethylated α‐Boryl Ketones. Issue 34 (22nd July 2016) - Lv, Wen‐Xin; Zeng, Yao‐Fu; Li, Qingjiang; Chen, Yunyun; Tan, Dong‐Hang; Yang, Ling; Wang, Honggen
Abstract: The synthesis of halogenated and trifluoromethylated α‐boryl ketones via a one‐pot oxidative difunctionalization of alkenyl MIDA boronates is reported. These novel densely functionalized organoborons bearing synthetically and functionally valuable carbonyl, halogen/CF3 and boronate moieties within the same molecule are synthetically challenging for the chemist, but have great synthetic potential, as demonstrated by their applications in a straightforward synthesis of borylated furans. The generality of this reaction was extensively investigated. This reaction is attractive since the starting materials, alkenyl MIDA boronates, are easily accessible. Abstract : α‐Boryl ketone synthesis : A one‐pot oxidative difunctionalization of alkenyl MIDA boronates for the syntheses of densely functionalized α‐boryl ketones was developed. The presence of multiple functional groups within the same molecule confers on these products great synthetic utility, as demonstrated by the successful synthesis of borylated furans.